2022
DOI: 10.1038/s41598-022-24508-8
|View full text |Cite
|
Sign up to set email alerts
|

Composite functional movement screen score predicts injuries in youth volleyball players: a prospective cohort study

Abstract: We aimed to investigate whether composite Functional Movement Screen (FMS) test scores can predict musculoskeletal injuries (MSI) in youth volleyball players. 131 national young volleyball players (Males: n = 100, age = 16.5 years, height = 1.787 m, mass = 68.32 kg; Females: n = 31, age = 13.83 years, height = 1.684 m, mass = 65.12 kg) participated in this prospective cohort study. The FMS screen was performed before starting the season. MSI and exposure data were collected during the season via each team’s ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Composite scores are created from the sum of individual tests within the screen, with some research suggesting cutoff scores for injury risk in certain populations. For example, a score at or below 14 on the FMS™ has been linked to increased injury rates, 7 while other authors have disputed the utility of this cutoff score. 8 The overhead squat is frequently included in movement screens, and is a component of the FMS™, AAA, and TPI screen.…”
Section: The Problemmentioning
confidence: 99%
“…Composite scores are created from the sum of individual tests within the screen, with some research suggesting cutoff scores for injury risk in certain populations. For example, a score at or below 14 on the FMS™ has been linked to increased injury rates, 7 while other authors have disputed the utility of this cutoff score. 8 The overhead squat is frequently included in movement screens, and is a component of the FMS™, AAA, and TPI screen.…”
Section: The Problemmentioning
confidence: 99%
“…Brumitt et al 20 reported that pre-season LEFT scores were associated with an increased risk of lower extremity injury in 193 male and female collegiate athletes but the results of another study conducted by the same research group on 395 athletes demonstrated that LEFT is not a suitable screening tool for predicting the risk of injury in division III athletes 20 , 21 . Shi et al 16 also demonstrated the reliability and validity of the LEFT for predicting low back or lower limb injury risk in the college athletes 19 . As this test is a quick test to administer, requiring minimal personnel, and no need for special equipment, the researchers demonstrated that it warrants further consideration as pre-participatory screening examination tool for sport injury in more specific athlete populations (i.e., a more homogenous athletic population rather than heterogeneous populations like division III athletes).…”
Section: Introductionmentioning
confidence: 98%
“…As this test is a quick test to administer, requiring minimal personnel, and no need for special equipment, the researchers demonstrated that it warrants further consideration as pre-participatory screening examination tool for sport injury in more specific athlete populations (i.e., a more homogenous athletic population rather than heterogeneous populations like division III athletes). Considering the contradictory results obtained from previous literature and the lack of focus of previous research on football (soccer) players, and the importance of developing the screening tests in pre-seasonal athletic activity 15 , 16 and physical therapy 22 , the present study aimed to investigate the probability of LEFT as a screening test to predict lower limb injuries in professional male footballers. Therefore, the purpose of this study was to investigate the screening value of the LEFT in predicting lower limb injuries in professional male footballers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing injury prevention programs in athletics activity is very important in order to reduce injuries 26 . The use of appropriate pre-sessional screening tools to identify injury-prone athletes is also very important in developing injury prevention programs 20 , 27 , 28 . Screening for the balance and proprioceptive ability of those athletes who participate in long-term training in the same sport is highlighted in previous studies specifically in order to acquire practical injury prevention strategies 11 , 20 .…”
Section: Introductionmentioning
confidence: 99%